Banking globalization: international consolidation and mergers in banking - Claudia M. Buch; Markus Spindler (Institut für Angewandte Wirtschaftsforschung (IAW), 2008)
This paper surveys recent literature on international mergers and acquisitions in banking. We focus on three main questions. First, what are the determinants of cross-border mergers of commercial banks? Second, do cross-border mergers affect the efficiency of banks? Third, what are the risk effects of international bank mergers? We begin with a brief summary of the stylized facts, and we conclude with implications for policymakers.
Keywords: F23; G21; 330; mergers and acquisition; international banking; survey